2010
DOI: 10.4097/kjae.2010.58.6.527
|View full text |Cite
|
Sign up to set email alerts
|

Caudal analgesia reduces the sevoflurane requirement for LMA removal in anesthetized children

Abstract: BackgroundAn anesthetic state can reduce adverse airway reaction during laryngeal mask airway (LMA) removal in children. However, the anesthetic state has risks of upper airway obstruction or delayed emergence; so possibly less anesthetic depth is advisable. Caudal analgesia reduces the requirement of anesthetic agents for sedation or anesthesia; it is expected to reduce the sevoflurane requirement for LMA removal. Therefore, we determined the EC50 of sevoflurane for LMA removal with caudal analgesia and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…; Kim et al. ), which could be a better explanation for the mechanism of temporary CNS signs related to the brain in the present study. Thoracic epidural lidocaine could be delivered to the brain via three potential pathways, including excessive cranial spreading in the epidural space, systemic circulation by vascular absorption (Lemke ), cranial diffusion via CSF in the subarachnoid space (Hodgson & Liu ; Xiao et al.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…; Kim et al. ), which could be a better explanation for the mechanism of temporary CNS signs related to the brain in the present study. Thoracic epidural lidocaine could be delivered to the brain via three potential pathways, including excessive cranial spreading in the epidural space, systemic circulation by vascular absorption (Lemke ), cranial diffusion via CSF in the subarachnoid space (Hodgson & Liu ; Xiao et al.…”
Section: Discussionsupporting
confidence: 57%
“…; Kim et al. ), or their combinations. However, the effect of epidural and systemic pathways were thought to be minor in our study, because the cranial border of the EB and SB did not reach the brain in the maps, and there was no behavior change after IV injection of lidocaine at the highest dose (4 mg kg −1 ) of the volumes evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Reduction of intraoperative maintenance requirement of inhalation anesthetic like sevoflurane by caudal blockade has been well-established. [ 3 4 5 6 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Numerous studies have shown this in cases, where volatile anesthetic namely Sevoflurane has been used for maintenance of intra-operative depth. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…have demonstrated that caudal analgesia reduces the sevoflurane concentration required for the LMA removal. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%